2015
DOI: 10.1093/nar/gkv1168
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic intron retention program enriched in RNA processing genes regulates gene expression during terminal erythropoiesis

Abstract: Differentiating erythroblasts execute a dynamic alternative splicing program shown here to include extensive and diverse intron retention (IR) events. Cluster analysis revealed hundreds of developmentally-dynamic introns that exhibit increased IR in mature erythroblasts, and are enriched in functions related to RNA processing such as SF3B1 spliceosomal factor. Distinct, developmentally-stable IR clusters are enriched in metal-ion binding functions and include mitoferrin genes SLC25A37 and SLC25A28 that are cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
212
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(235 citation statements)
references
References 43 publications
20
212
0
Order By: Relevance
“…In 9980 of these samples with PTC containing IRs, we observed a higher negative correlation coefficient between change in IR and change in expression than that observed for the in-frame IRs (permutation test P = 0.002; Figure 2F). Together, these results suggest a role for IR in sex-biased expression, and are consistent with previous reports indicating that IR can negatively tune gene expression (BRAUNSCHWEIG et al 2014;DVINGE AND BRADLEY 2015;PIMENTEL et al 2016). Finally, GO analysis showed that genes with testis-biased IR were enriched in oogenesis, neurogenesis, female gamete generation, and others (Table S3, hypergeometric test P < 0.001).…”
Section: Introns That Are Differentially Retained In Ovary and Testissupporting
confidence: 91%
See 4 more Smart Citations
“…In 9980 of these samples with PTC containing IRs, we observed a higher negative correlation coefficient between change in IR and change in expression than that observed for the in-frame IRs (permutation test P = 0.002; Figure 2F). Together, these results suggest a role for IR in sex-biased expression, and are consistent with previous reports indicating that IR can negatively tune gene expression (BRAUNSCHWEIG et al 2014;DVINGE AND BRADLEY 2015;PIMENTEL et al 2016). Finally, GO analysis showed that genes with testis-biased IR were enriched in oogenesis, neurogenesis, female gamete generation, and others (Table S3, hypergeometric test P < 0.001).…”
Section: Introns That Are Differentially Retained In Ovary and Testissupporting
confidence: 91%
“…Intron retention (IR) is a type of AS event in which one or more introns are retained in the mRNA molecule. IR is the dominant AS type in Drosophila (GRAVELEY et al 2011) and affects about half of all introns in mammals (WONG et al 2013;BRAUNSCHWEIG et al 2014;EDWARDS et al 2016;PIMENTEL et al 2016). The "anomalous" mRNA generated by the retention of an intron may contain a premature termination codon (PTC) (JAILLON et al 2008), which can sometimes result in the degradation of the mRNA by the nonsense-mediated mRNA decay (NMD) pathway.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations